Apartheid's Alcatraz: the Barberton Prison Complex during the early 1980s - Part two - Peté, Stephen Allister (My University, 2015)
The purpose of this two-part article is to examine in detail the public discourse surrounding the Barberton Prison Complex during the early 1980s, at the height of the apartheid era. The prisons within the Barberton Prison Complex were notorious as being among the most punitive of the many prisons within apartheid South Africa. Barberton was the place to which the most dangerous and intractable prisoners were sent to serve their sentences, making it apartheid's "Alcatraz". The focus of this article is on the treatment of "normal" as opposed to "political" prisoners during the period in question, allowing the "voices" of ordinary prisoners - often sidelined and silenced - to be brought to the fore. The Barberton Prison Complex is examined through the lens of public discourse, as reflected in a wide range of South African newspapers published at the time. By analysing a large number of reports dealing with events at Barberton during the period in question, in both English and Afrikaans language newspapers, as well as in both politically conservative and politically liberal newspapers, this article attempts to capture both the "smell" and the "feel" of what it was like to be imprisoned in one of apartheid's toughest prison complexes. Furthermore, this article seeks to show that - despite legislative measures restricting the publication of information on conditions inside apartheid prisons - the press was able to provide a steady stream of information to the South African public on the shocking events which occurred at Barberton during the period in question. Part Two of the article examines a string of violent incidents which occurred within the Barberton Prison Complex during the course of 1983, leading to nine inmate deaths. The response of the authorities to this orgy of violence at Barberton is discussed, including the findings of a committee of enquiry. It is concluded that the events at Barberton during the early 1980s were symptomatic of what was happening to the apartheid system as a whole. The South African penal system - in particular at its harshest extremity - acted as a kind of barometer, revealing both the cruelty of the system, as well as the considerable constraints and pressures under which it was operating.
Keywords: Barberton Prison Complex; Barberton Prison Farm; Prison violence; Apartheid prisons; Prison deaths; Prison torture; Prisoner heat exhaustion; Heat exhaustion trial